Immunization with Brugia malayi Hsp70 protects mice against Litomosoides sigmodontis challenge infection. (April 2014) - Hartmann, W.; Singh, N.; Rathaur, S.; Brenz, Y.; Liebau, E.; Fleischer, B.; Breloer, M.
Summary More than 1·5 billion people are at risk of being infected with filarial nematodes worldwide. Therapy and control of transmission are mainly based on mass drug distribution. As these drugs have to be administered annually or biannually and might be loosing their efficacy, a vaccine against filariae is an alternative approach to chemotherapy. In the current study, we have analysed the potential of Brugia malayi heat shock protein 70 (BmHsp70) as a vaccine candidate in a murine helminth infection. Immunization of BALB/c mice with alum‐precipitated recombinant BmHsp70 conferred partial protection against subsequent challenge infection with the rodent parasite Litomosoides sigmodontis. Immunization resulted in reduced numbers of larvae in the pleural cavity as well as reduced numbers of circulating microfilariae. Reduced parasite burden was associated with high titres of BmHsp70‐specific antibodies and increased production of type I and II cytokines in response to L. sigmodontis antigen and BmHsp70. In summary, the immunization with BmHsp70 induced cellular and humoral immune responses and partially protected against L. sigmodontis in a challenge infection. Therefore, we hypothesize that BmHsp70 might be considered as a potential vaccine candidate for reduction in the incidence of B. malayi infections in future studies.